Κ-Carbide assisted nucleation of B2: A novel pathway to develop high specific strength steels. (November 2021) - Zargaran, A.; Trang, T.T.T.; Park, Gyeongbae; Kim, Nack J.
Abstract: Controlling morphology of B2 phase as nano-sized particles that are homogenously distributed within austenite matrix has been remained as a challenging task particularly for hot rolled lightweight steels, where the nucleation sites for B2 precipitation are less abundant than in cold rolled ones. Utilizing the phenomena occurring in age-hardenable aluminum alloys, i.e., heterogeneous nucleation of precipitates from pre-existing GP zones, here we solved this challenge by using κ-carbide nanoparticles to promote the formation and to engineer the morphology of B2. This strategy has been applied to a hot rolled Fe-21Mn-10Al-1C-5Ni model steel resulting in the formation of a large fraction of B2 nanoparticles (sizes of 20-500 nm) uniformly distributed within austenite grains. Besides their contribution to precipitation strengthening, these B2 nanoparticles lead to a dramatic improvement of work hardening capability of the steel. As a result, novel precipitation hardened hot rolled lightweight steel with excellent combination of ultrahigh specific strength and ductility has been fabricated. Such properties of the present steel are not only better than those of other hot rolled lightweight steels strengthened by B2 and/or κ-carbide but also comparable to those of the steels subjected to additional cold rolling, and it is expected to expand the applications of B2-strengthened steels in response to an increasing demand for lightweight constructions. Graphical abstract: Image, graphical abstract